Peningkatan Pemahaman Konsep Perkalian Melalui Penggunaan Media Kartu Bilangan pada Siswa Kelas III Sekolah Dasar - Junaidi Junaidi; Suci Permata Sari (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to enhance third grade elementary school students’ conceptual understanding of multiplication through the implementation of number card media. The study was motivated by the low level of students’ conceptual comprehension, as learning practices were predominantly procedural and focused on memorizing multiplication facts rather than understanding multiplication as repeated addition and grouping. This research employed Classroom Action Research (CAR) consisting of two cycles, each including planning, action, observation, and reflection stages. The participants were eight third grade students. Data were collected through observation sheets and achievement tests, and analyzed using descriptive quantitative analysis complemented by qualitative reflection. The findings indicate a substantial improvement in students’ conceptual understanding. Learning mastery increased from 62.5% in the first cycle to 87.5% in the second cycle. The use of number card media facilitated active student engagement, promoted concrete representation of abstract mathematical concepts, and supported meaningful learning processes. The results suggest that instructional media grounded in concrete and manipulative approaches significantly contribute to strengthening students’ mathematical conceptualization. Therefore, number card media can be considered an effective pedagogical strategy to improve multiplication concept understanding at the elementary school level. Keywords : conceptual understanding, multiplication, number card media